Modelling the Caribbean macro economy for forecasting and policy analysis - Maurin, Alain ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Looks at the various alternative approaches available for modeling the Caribbean economy. Examines their potential for economic forecasting and policy simulations.